Is a quantifier mismatch a problem for L1 Japanese learners of English? - Nehls, Paul N.; Aramaki, Kodai; Fujii, Tomohiro (LingBaW. Linguistics Beyond and Within, 2023)
After identifying a linguistic difference between the English quantifier most and the Japanese quantifier hotondo ‘most’ we set out to find if the semantic difference between the two would constitute a learning problem for Japanese second language (L2) learners of English. The difference we hypothesized between the two is that English most is considered “more than half,” while hotondo is “nearly all.” As this semantic difference is not explicitly taught in a classroom environment, acquisition by learners would need to take place through experiencing most in contexts where they might receive contextual clues. An examination of a corpus indicated that contextual clues towards such a semantic difference would be unavailable or rarely available. Two sets of experiments (Experiments 1 and 2) were conducted using the Truth Value Judgment Task methodology. The results of Experiment 1 showed that L2 speakers treated most as meaning “nearly all” but that the level of learner proficiency has an effect. The upper intermediate L2 learner group (Experiment 1a) behaved more like the L1 English speaker group (Experiment 1b) than the lower proficiency L2 group (Experiment 1c). Experiment 2, testing Japanese L1 speakers on their interpretation of Japanese hotondo ‘most,’ revealed that while a majority of participants treated hotondo as “almost all,” there was, somewhat unexpectedly, a group of speakers who interpreted hotondo to mean “more than half.” Therefore, although the possibility cannot completely be eliminated that the result of Experiment 1a is due to L1 transfer, if some Japanese learners of English can unlearn the incorrect meaning, then some prior, if not innate, knowledge that makes the process possible must be available to them.